Essays on high-frequency market microstructure: Herding and volume-synchronized probability of informed trading - Laurs Randbøll Leth (University of Copenhagen, Department of Economics, 2019)
This thesis consists of three single-authored chapters on high-frequency market microstructure. All of them are self-contained, and can be read independently. Chapter 1 examines the extent of herd behavior in a financial market from 2005 to 2008; in particular, whether herd selling increased during 2007 and 2008, consistent with a stock market crash. Chapter 2 investigates how portfolio hedging can take advantage of a microstructure measure (VPIN) of toxic order ow. Finally, Chapter 3 presents a study of parametric estimation of this measure. In the following, concepts and state of the art of market microstructure are reviewed, and the three chapters are introduced.
Keywords: 330